Using Instagram for Library Information Marketing to Enhancing Institutional Image Among Generation Z - Muhammad Rasyid Ridlo; M. Fahmi Irawan; Cut Salsabilla; Syailaisa Chairatu; Annisa Intan Zakira (Record and Library Journal, 2026)
Background of the study: Academic libraries are no longer understood solely as repositories of information, but as adaptive institutions that must respond to the digital habits and media consumption patterns of Generation Z. Purpose: This study aims to examine the use of Instagram as an information marketing platform in academic libraries and its contribution to strengthening institutional image among Generation Z users through the Uses and Gratifications (U&G) framework. Method: This study employed a Systematic Literature Review (SLR) design guided by PRISMA procedures. From approximately 1,300 initially identified records, 50 peer-reviewed empirical studies were selected for qualitative synthesis. The data were analyzed using the four dimensions of the Uses and Gratifications framework. Findings: The findings indicate that Instagram supports academic libraries in delivering timely information, presenting visually engaging content, facilitating two-way communication, and strengthening institutional identity among Generation Z users. However, user engagement remains largely transactional, with limited personalization and participatory interaction. Conclusion: To strengthen institutional image and user engagement, academic libraries should move beyond one-way information dissemination and adopt more participatory, personalized, and collaborative Instagram communication strategies. Such approaches are essential for maintaining institutional relevance and strengthening relationships with Generation Z in the digital era.